Persepsi dan Minat Mahasiswa Fakultas Pertanian di Kabupaten Jember terhadap Profesi Petani - Deva Jaya Perkasa; Henik Prayuginingsih; Nurul Fathiyah Fauzi (Jember University Press, 2023)
Agriculture is an important sector because it produces the food, shelter, and clothing needed by the community. The agricultural sector is still less attractive to the younger generation, even to the Faculty of Agriculture students themselves. The reasons for the lack of interest in the agricultural sector are due to several things, namely the stigma that agriculture is poor, the perception that agriculture is dirty, dangerous and difficult, and the news about crop failures. This study aims to identify: (1) the perceptions of students of the Faculty of Agriculture in Jember Regency towards the farming profession; (2) the interest of students in the Faculty of Agriculture in Jember Regency towards profession of farmers; (3) the relationship between perceptions and the interest of students of the Faculty of Agriculture in Jember district towards profession of farmers. This research uses descriptive analytical method. The data used are primary and secondary data, analyzed using a descriptive analysis with Likert scale and Rank Spearman Correlation. The number of research samples are 20 studenst of Jember Muhammadiyah University (UM Jember), 62 studenst of Jember University (UNEJ), and 15 studenst of Jember Islamic University (UIJ). The results are: (1) students of the Faculty of Agriculture in Jember Regency had a good perception of the farming profession with a percentage value of 70.83%; (2) students of the Faculty of Agriculture in Jember Regency are very interested in working as farmers with a percentage value of 77.74%; (3) the perception with interest of the students of the Faculty of Agriculture in Jember Regency has a significant relationship to the farming profession with a value of rs = 0.519 which is classified as a category of quite large or quite strong relationship.